Development and performance examination of an integrated plant with desalination process for multigeneration purposes. (15th July 2021) - Yilmaz, Fatih; Ozturk, Murat; Selbas, Resat
Highlights: A novel gas turbine-based system integrated with a desalination unit is proposed. Examining the thermodynamic and environmental impact analyses of integrated plant. Single-generation produces 37% more carbon dioxide emissions than multi-generation. The energy and exergy efficiencies of the integrated system are 0.6076 and 0.5671. Abstract: Increasing environmental problems are of great importance in the development of efficient energy utilization. This article proposed an innovative design gas turbine-based multi-generation plant that integrating a desalination unit for advanced energy management and utilization. Furthermore, this modeled plant comprises a Brayton cycle, a reheat Rankine cycle, an organic Rankine Cycle which does with ammonia, a greenhouse, a Proton Exchange Membrane electrolyzer, and a desalination component. The main purpose of this study is also to provide beneficial commodities such as energy, hydrogen, heating, freshwater, in addition to this to reduce the emission rate by integrating different subsystems, and also to increase system performance. On the other hand, comprehensive thermodynamic assessment and environmental impact evaluation are made that are energy efficiency, exergy efficiency, carbon dioxide emission rate, and sustainability index evaluations, for the overall model and sub-systems. The conclusions of the analysis demonstrated that the whole plant's energy and exergy effectiveness are determined as 0.6076 and 0.5671, respectively, while the carbon dioxide emission rate of the planned model is 0.31 t/MWh. The whole irreversibility of the advised model is 2679.09 kW, and also the maximum exergy destruction rate is found in the combustion chamber with 1216 kW. Moreover, the proposed configuration system has a hydrogen production amount of 0.001742 kgs −1 and a clean water production amount of 0.7647 kgs −1 .